Behavior of Several Peanut Genotypes Under Sunlight and Water Deficit Condition - Hemon, A. Farid; Sumarjan, Sumarjan; Ujianto, Lestari; Listiana, Baiq Erna; Yakop, Uyek Malik (Journal of Science and Science Education, 2024)
Drought and shade stress often occur together in peanut plants. Sunlight and water are the main factors that determine the growth of peanut plants. This study aimed to determine the behavior of several peanut genotypes under conditions of sunlight and water deficit. This research was conducted using a Completely Randomized Design-Split Plot Design with three replications. The treatments to be tested were double stresses (sun light and water deficit) and no stress (control) factors as the main plot and peanut genotype factors, namely Takar-1, Domba, Bison, G2T5, and G19-UI as subplots. The results showed that the peanut genotypes had different behaviors under double stresses (sunlight and water deficit). Peanut plants under double stress caused a reduction in pod dry weight, number of pods, root dry weight, and chlorophyll-a levels compared to those without stress. Peanut genotype G19-UI resulted in the lowest percentage reduction in pod dry weight and number of pods per plant, namely 58.79% and 43.75% under double stresses, respectively